Evaluation of the Norwegian R&D tax credit scheme - Ådne Cappelen; Erik Fjærli; Frank Foyn; Torbjørn Hægeland; Jarle Møen; Arvid Raknerud; Marina Rybalka (Statistics Norway, Research Department, 2010)
We find that the Norwegian R&D tax credit scheme introduced in 2002 mainly works as intended. The scheme is cost-effective and it is used by a large number of firms. It stimulates these firms to invest more in R&D, and, in particular, the effect is positive for small firms with little R&D experience. The returns on the R&D investments supported by the scheme are positive and generally not different from the returns to other R&D investments. We have found examples of what can be interpreted as tax motivated adjustments to the scheme, but to some extent this must be accepted as a cost to subsidy and support schemes intended for use by a large number of economic agents. This is particularly so when attempts are made to keep administrative expenditures and control routines at a low level.
Keywords: H25; O38; 330; R&D tax credit; R&D subsidies; Innovation policy; Norway